KEWENANGAN MAHKAMAH KONSTITUSI REPUBLIK INDONESIA DALAM PEMBENTUKAN NORMA BARU (SUATU KAJIAN TERHADAP PUTUSAN MAHKAMAH KONSTITUSI NOMOR 21/PUU-XII/2014 JO PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-XIV/2016) - Elisabet .; Cut Memi (Jurnal Hukum Adigama, 2018)
One of the authorities of the Constitutional Court governed by the Constitution of the Republic of Indonesia in 1945 was the examining of laws against the contitution or judicial review. Inside the regulations which governing the implementation of this authority, the Constitutional Court only acts as a negative legislator, namely canceling or reinforcing a norm tested by the Petitioner. But in practice, the Constitutional Court has changed its role to become a positive legislator, who is forming a new legal norm, which is the authority of legislators. The Constitutional Court should not be able to form a new legal norm because there is no legal basis which regulate that. But Constitutional Court can form a new legal norm in some urgent circumstances, relating to Human Rights, and preventing legal vacuum. In addition, the establishment of laws by lawmakers that require a long process and time. This is compelling Constitutional Court to make substitute norm before the law was established by the legislators. In the Decision of the Constitutional Court Number 46/PUU-XVI/2016, the Court actually wants to establish a new legal norm, but because the articles in the petitioned have criminal sanctions, and if the Constitutional Court approves the petition, the Constitutional Court has formulated a new criminal act that can only be formed by the lawmaker. Whereas in the Decision of the Constitutional Court Number 21/PUU-XII/2014, the Constitutional Court established a new norm because in the article a quo there were no criminal sanctions.